Pattern of adverse drug reaction to antiepileptic drugs in a tertiary care hospital - Akalu, Suchitra D.; Belavadi, Niveditha G. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Adverse drug reactions (ADRs) are a major cause of morbidity and mortality, and are the leading cause of hospital admission. The overall rate of ADRs is estimated to be 6.5% and 28% of these ADRs are preventable. Antiepileptic drugs (AEDs) are authorized for several therapeutic indications and are highly prescribed. ADRs due to AEDs range from minor maculopapular exanthem (MPE) to severe life-threatening reactions like Drug reaction eosinophilia and systemic symptoms (DRESS) and Stevens-Johnson syndrome (SJS). Objective of the study was to evaluate the pattern of ADRs reported with AEDs in an adverse drug reaction monitoring centre (AMC) of a tertiary care hospital. Methods: Retrospective analysis of the records was done for a period 48 months from January 2013 to December 2016. During this period, all the ADRs caused by AEDs reported to the AMC were included in the study. The study evaluated the pattern of ADRs due to AEDs. The study also assessed the gender-wise distribution, predilection for various systems, causality, severity, and preventability of ADRs. Data was analysed using descriptive statistics. Results: A total of 319 ADRs were reported by spontaneous reporting during the entire study period. Out of the total 319 ADR reports received, antiepileptic drugs related ADRs were 35 (11%). Antiepileptic drugs which caused the ADRs included phenytoin, carbamazepine, clobazam and lorazepam. The most common system affected was dermatological (60%), followed by gastrointestinal system (17.14%), vascular system (11.42%), blood (5.8%), respiratory system (5.8%) and central nervous system (2.9%). Among the dermatological ADRs, SJS accounted for 11 cases of which 10 cases were due to phenytoin and one case was due to carbamazepine. DRESS syndrome due to phenytoin was documented in one case. Conclusions: AEDs are the most commonly prescribed drugs for various indications. Uses of AEDs are accompanied by ADRs which vary from mild rashes and itching to SJS and DRESS/TEN. Post-marketing surveillance of the AEDs is important for compliance, therapeutic efficacy and ultimately safety of the patient.